Acess Skills in Fiction - Wren, Wendy (Delta : Nelson Thornes, 2005)
A lower ability companion to the middle/higher ability NTFE core course at three Key Stage 3 Levels (Year 7, 8, 9). Twin-track (Fiction / Non-Fiction) student books with a photocopiable resource book and teacher's guide.
Keywords: Anglais (Langue); Composition et exercices; Ouvrages pour la jeunesse